Further Notes on Fishing and Simple Commodity Production in Western Venezuela - Carrillo, Jorge; Suárez, María Matilde (Anthropologica, 2022)
This paper intends to show how two perspectives some times considered as mutually exclusive can be used simultaneously in order to acquire a deeper understanding of a historical process. Using data from fishing communities of Western Venezuela it is shown that external articulation and formal subsumption of a simple commodity production are merely complementary ways of looking at the same process.